THEORIES OF CRIME IN PRINT MEDIA: AN ASSIGNMENT - Novak, Katherine (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
For this assignment, you will need to find a newspaper or magazine article that discusses a crime. The article you choose needs to go into some detail concerning the nature of the crime and offer some explanation for why the individual(s) involved are believed to have committed the crime.